Water Resources Management VII 2013
DOI: 10.2495/wrm130191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water warming on bank filtration: experimental enclosure studies

Abstract: In the context of climate change artificial recharge of groundwater becomes increasingly important. The two main climate change factors affecting ground water recharge performance are water warming and extreme precipitation events with drought and floods. This will strongly influence self-purification processes, indirectly due to changes in the stratification and circulation characteristics of the lake and directly due to the intensification of metabolic processes and biodegradation efficiency, which are respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The findings regarding the minimum and maximum changes in LSWT (MinLSWT and MaxLSWT), indicate that different months exhibited varying temperature increases and variability levels within each period. A similar result has been observed in Poland and in other parts of central Europe [29,30,[38][39][40][41][42][43]. The months with the highest variability suggest periods when temperature fluctuations were more pronounced and vice versa, which could be attributed to various factors.…”
Section: Discussionsupporting
confidence: 82%
“…The findings regarding the minimum and maximum changes in LSWT (MinLSWT and MaxLSWT), indicate that different months exhibited varying temperature increases and variability levels within each period. A similar result has been observed in Poland and in other parts of central Europe [29,30,[38][39][40][41][42][43]. The months with the highest variability suggest periods when temperature fluctuations were more pronounced and vice versa, which could be attributed to various factors.…”
Section: Discussionsupporting
confidence: 82%
“…Kangur et al (2013) observed an increase in maximum water temperature in the summer period for Lake Peipsi (Estonia/ Russia). In a broader perspective the response of lakes to climatic changes in this part of Europe is similar to many other cases located in different regions of the world (Austin and Colman, 2007;Hampton et al, 2008;Shimoda et al, 2011;Groß-Wittke et al, 2013;Zhong et al, 2016;Haddout et al, 2018). For instance, for the summer period (July-September) the surface water temperature in the Great Lakes in North America experienced a warming trend at a rate of 1.1 °C dec -1 (Austin and Colman, 2007).…”
Section: Discussionmentioning
confidence: 63%
“…Increasing water temperatures lead to decreased oxygen concentrations with increasing oxygen consumption by organisms; this means the oxygen balance is worsened, and the risk of anaerobic conditions is raised. Studies on temperature effect on bank filtration were conducted in Lake Tegel, Berlin/Germany using heated enclosures, resulting in a water temperature increase of 5 • C and an increase of sediment temperature of 2-3.5 • C [13]. The redox state of the infiltration zone was changed and characterized by a decline of oxygen concentrations within the interstices.…”
Section: Climate Change Effects On Drinking-water Sourcesmentioning
confidence: 99%
“…Increasing water temperatures of rivers mainly in shallow littoral zones, where groundwater recharge occurs, can impact bank filtration efficiency because water temperature regulates bio-chemical processes. Key factors for bank filtration efficiency are the temperature tolerance of organisms, increasing biomass of interstitial flora and fauna, intensification of turnover of organic carbon, and, as a consequence, increased biochemical consumption of oxygen [13]. In general, we can apply the temperature rate of the reaction rule; this means that an increase of 10 • C leads to biochemical reactions two or three times faster, which corresponds to an increase of 10-20% per • C. In addition, climate change effects, such as long-lasting droughts or flood events, influence bank filtration, but only few studies are available [13,14].…”
Section: Introductionmentioning
confidence: 99%